1918
DOI: 10.1084/jem.28.4.449
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Antimeningitis Vaccination and Observations on Agglutinins in the Blood of Chronic Meningococcus Carriers

Abstract: 1. A meningococcus vaccine suspended in salt solution has been given subcutaneously as a prophylactic to about 3,700 volunteers in three injections of 2,000 million, 4,000 million, and 4,000 or 8,000 million cocci at weekly intervals. 2. These doses rarely caused more than the mildest local and general reactions. Exceptionally a more severe reaction emphasized the presence of an unusual individual susceptibility to the vaccine. In such instances the symptoms were in part those of meningeal irrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1919
1919
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…However, just five days later, there was little willingness to receive a second injection until they were threatened with cancellation of upcoming leave. 33 In four studies in which the investigators actively solicited adverse events, 15,17,19,33 both local and systemic reactions were more severe than described in other reports.…”
Section: 32mentioning
confidence: 94%
See 4 more Smart Citations
“…However, just five days later, there was little willingness to receive a second injection until they were threatened with cancellation of upcoming leave. 33 In four studies in which the investigators actively solicited adverse events, 15,17,19,33 both local and systemic reactions were more severe than described in other reports.…”
Section: 32mentioning
confidence: 94%
“…8 Over the next twenty years, up until the availability of sulfa chemoprophylaxis, similar vaccines were employed in the context of meningococcal outbreaks, being 45 types I and III under the Gordon-murray scheme correspond to what is now termed group A; type II refers to groups B and C, a distinction not being made until the 1940s, after which type II corresponds to group B and type IIa to group C. 45,46 As for duration of protection, Black observed that six out of seven vaccinees still had measurable complement fixation titers at two years post-vaccination. 28 Cases that developed after the full threedose regimen were observed at two 15 and six months 29 after the final dose with few studies maintaining follow-up for longer periods. Brutsaert believed that immunity from vaccination was short-lived, requiring at least two vaccinations to be given annually.…”
Section: Whole Cell Vaccination For Meningococcusmentioning
confidence: 99%
See 3 more Smart Citations